CELL DISTRUPTION MIKROALGA SECARA ENZIMATIS DENGAN SELLULASE - Padil Padil; Siti Syamsiah; Muslikhin Hidayat; Rina Sri Kasiamdari (Dept. of Chemical Engineering, Diponegoro University, 2015)
ENZYMATIC CELL DISRUPTION OF MICROALGAE USING CELLULASE. Micro-algae is one source of potential alternative energy of third generation to be developed as bioethanol raw material. The starch content trapped in Micro-algae cell walls causing the need of cell distruption to release and convert starch into simple glucose before the fermentation process. This study aims to open up the cell walls of Micro-algae and to explore the effect of sellulase enzymes from Aspergillus niger as Micro-algae cell distruption strategy as well as the optimization of process parameters, i.e the concentration of enzyme, temperature, pH, and time which produce the highest glucose yield. The results showed that the highest glucose yield was 82.44% (w/w) obtained at an enzyme concentration of 30% (w/w), temperature 45oC, pH of 4.5 at 40 minutes, the amount of Micro-algae as 0.5 g/L. In general, cell distruption method using sellulase enzyme was proven to be a promising option to open the cell walls of Micro-algae and convert cellulose into simple glucose simultaneously in producing bioethanol. Keywords: bioethanol; cellulose; cell distruption; enzymatic; micro-algae; starch Abstrak Mikroalga merupakan salah satu sumber energi alternatif generasi ketiga yang potensial untuk dikembangkan sebagai bahan baku bioetanol. Kandungan pati yang terperangkap dalam dinding sel mikroalga menyebabkan perlunya cell distruption untuk melepaskan sekaligus mengkonversi pati menjadi glukosa sederhana sebelum proses fermentasi. Penelitian ini bertujuan untuk membuka dinding sel mikroalga sekaligus mengeksplorasi pengaruh enzim sellulase dari aspergillus niger sebagai strategi cell distruption mikroalga serta melakukan optimasi parameter proses yaitu konsentrasi enzim, suhu, pH, dan waktu yang memberikan yield glukosa tertinggi. Hasil penelitian menunjukkan bahwa yield glukosa tertinggi adalah 82,44% (w/w) yang diperoleh pada konsentrasi enzim 30% (w/w), suhu 450C, pH 4,5 pada waktu 40 menit, dengan jumlah mikroalga 0,5 g/L. Secara umum, metode cell distruption dengan menggunakan enzim sellulase terbukti menjadi pilihan yang menjanjikan untuk membuka dinding sel mikroalga sekaligus mengkonversi selulosa menjadi glukosa sederhana dalam memproduksi bioetanol.